Pemanfaatan Media Online Quizizz Untuk Meningkatkan Kemampuan Menghafal Perkalian Dasar Siswa SD - Anindita Dwi Ratriningrum (CV. Ulil Albab Corp, 2022)
Based on observations during the mathematics learning process, 6th grade students of SD Negeri 5 Prajegan have a weakness in basic multiplication so that it affects the process of working on problems related to multiplication. In this study, researchers wanted to use Quizizz's online media as a game-based multiplication memorization method to improve students' basic multiplication memorization skills. This research was carried out in 2 cycles with the design in each cycle including planning, implementation, observation, and reflection. At the end of the study, a questionnaire was also filled out to find out student responses regarding the use of Quizizz online media to improve memorization of basic mathematical multiplication. From this study it can be concluded that through the use of online media Quizizz can improve students' basic multiplication memorization skills.